Implementasi Unsur Alasan Pemaaf dan Pembenar dalam Kekerasan di Lingkungan Pendidikan - Bastyan, Almira Carissa; Tjoneng, Arman (University of Merdeka Malang, 2023)
In Indonesia today, violence against students in the educational environment is considered a dishonorable act, this is because with the birth of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, it was formed with the aim of protecting the rights of children wherever they are, including in the school environment. But in reality there are still violations of children's rights, especially in the school environment. The writing in this study uses normative juridical research methods that focus on principles, rules, applicable legal regulations that aim to find out how violence forms and how to solve the problems caused. The results showed that violence against children in the school environment is a form of non-optimal application of the Child Protection Law, and effective steps to resolve it can be done through legal channels (litigation) and non-legal channels (non-litigation) by looking at how severe the form and level that causes the impact of violence and others